Primeiro registro da cochonilha Lecanodiaspis dendrobii Douglas, 1892 (Hemiptera: Coccoidea: Lecanodiaspididae) e do parasitoide associado Cephaleta sp. (Hymenoptera: Pteromalidae) no Brasil - Marsaro, A. L.; Peronti, A. L.B.G. [UNESP]; Costa, V. A.; Morais, E. G.F.; Pereira, P. R.V.S. (FapUNIFESP (SciELO), 2016)
Lecanodiaspis dendrobii Douglas, 1892 (Hemiptera: Coccoidea: Lecanodiaspididae) and the associated parasitoid Cephaleta sp. (Hymenoptera: Pteromalidae) are reported for the first time in Brazil. Specimens of this scale insect were collected on branches and stems of Acacia mangium Willd., Leucaena leucocephala (Lam.) de Wit (Fabaceae), Morus nigra L. (Moraceae), Citrus reticulata Blanco (Rutaceae), Tectona grandis L. f. (Verbenaceae), Anacardium occidentale (Anacardiaceae), Annona squamosa L. andXylopia aromatica (Lam.) Mart. (Annonaceae), in three municipalities of the Roraima state. All plants here mentioned are recorded for the first time as a host for L. dendrobii. Morphological characters of L. dendrobii and symptoms presented by the host plants infested by this pest are included in this work.
First report of lecanodiaspis dendrobii douglas, 1892 (Hemiptera: Lecanodiaspididae) and the associated parasitoid cephaleta sp. (hymenoptera: Pteromalidae) in Brazil
Keywords: Fabaceae; Moraceae; Pest of quarantine importance; Rutaceae; Verbenaceae